ANALISIS OPTIMASI PENGGUNAAN FAKTOR PRODUKSI KOPI BUBUK PADA AGROINDUSTRI XYZ DI KOTA JAMBI - Riri Oktari Ulma; Dewi Sri Nurchaini; Yusma Damayanti (Universitas Sebelas Maret, 2021)
This research was aimed to determine the use of production factors optimal coffee beans and labor in the coffee powder agroindustry. The results showed that each additional raw material for coffee beans by 10% will increase the production of powder coffee by 4.09%, while the addition of labor will increase the production of powder coffee by 4.14%. The use of coffee bean raw material production factors can be added up to an optimal limit of 28,876.35 kg/quarter or there is an increase of 23.68% in the actual use. In one month the optimal limit is the amount of raw material used to be 9,625.45 kg or 385.02 kg per day. The use of labor can be added up to an optimal limit of 114 working people (HOK) or an increase of 25.30% of the actual use of labor. Calculated in working hours, the optimal use of working hours is 17,100 working hours per quarter or 5,700 working hours per month. Within one workday the limit for the optimal use of work is 228 hours with the number of workers being ± 38 people. The optimum amount of production is 27,354.32/quarter, an increase of 5,165.02 kg (23.28%) of actual production. The optimum profit increased by Rp 335,257,566.67 or 23.68% of the actual profit.